The Effectiveness of Using the Reggio Emilia Approach on the Experimental Science Lesson for Third-Grade Elementary Students - Batool Sabzeh; Farangis Ghalavand; Seyedamir Ghasemtabar (رویکردهای نوین آموزشی)
The current research aims to survey the effect of applying the Reggio Emilia approach on the learning of experimental sciences in the third grade of elementary school. This research was conducted as a quasi-experimental method with a pre-test-post-test design and a control group. The statistical population of the study was formed by the third-grade students of Andimeshk City in the academic year 1402-1401. Among them, the third-grade students of Modares boys' primary school were selected and randomly 50 of them were placed in two experimental and control groups. The experimental group was inspired by the Reggio Emilia approach and the control group was trained with the usual method for 15 sessions. Data collection was done using a researcher-made test of the science lesson and functional checklist. Teachers and professors confirmed the validity of the tool and its reliability was obtained through Cronbach's alpha test of 0.865. The results of the multivariate covariance analysis showed that the Reggio Emilia approach increased the learning rate of third-grade elementary students in the science course in all three levels of facts (F=309.81; P=0.001), basic concepts and skills (F=150.67; P=0.001). P=0.001), the use of learning in new situations (F=144.26; P=0.001), and the whole (F=279.98; P=0.001) has significantly increased. Additionally, the effect size indicated that overall, 85% of the difference between the experimental and control groups is attributable to the experimental intervention, which was the implementation of the Reggio Emilia approach (p< .001). This study showed that by using the Reggio Emilia approach as an exploratory, formative, and constructivist approach, students' learning can increase in all three levels of learning (facts; basic concepts and skills; and applying what they have learned in new situations). Therefore, it is suggested to use and check the effectiveness of this approach for other courses and educational levels of the elementary school.IntroductionScience education has been an integral part of the elementary school curriculum since the 19th and 20th centuries, influenced by the work of scholars such as Whewell, Dewey, and Schwab (Matthews, 2018). A primary goal of science education is to foster scientific literacy for addressing real-world problems (Krajcik & Czerniak, 2014). Achieving this goal necessitates the cultivation of scientific ideas (knowledge acquisition), skills, attitudes, and a connection to the surrounding world (Harlen & Qualter, 2004). Researchers argue that methods like project-based learning, which align with constructivist principles, offer a promising approach to science education. These methods provide authentic inquiry experiences and can leverage technology to enhance learning (Barak & Dori, 2005 as cited in AL-Balushi & AL-Aamri, 2014). This study focuses on the Reggio Emilia approach, a constructivist and inquiry-based approach rooted in the theories and experiences of scholars like Dewey, Bruner, Vygotsky, and Piaget. The Reggio Emilia approach can serve as an effective method for transitioning from traditional, memorization-based teaching to meaningful and deep learning that aligns with the unique needs and abilities of learners in science education. Accordingly, this research aims to examine the impact of implementing the Reggio Emilia approach on third-grade students' science learning.MethodologyThis study employed a quasi-experimental design with a pre-test-post-test and non-equivalent control group. The population of the study consisted of third-grade elementary students in Andimeshk city during the 2023-2024 academic year. From this population, Modarres Boys' Elementary School, with 100 third-grade students, was selected as the sample. Fifty students were randomly assigned to two groups: experimental (n=25) and control (n=25). The experimental group received instruction inspired by the Reggio Emilia approach, while the control group received traditional instruction for 15 sessions. For the experimental group, the first stage focused on initiating projects, followed by research, information gathering, classification, and finally, conclusion and documentation. Three lessons from the third-grade science textbook were selected for this study. Based on the science textbook's schedule, five sessions were allocated to each lesson. The first session of each lesson focused on initiating projects, while the second, third, and fourth sessions were dedicated to research and information gathering. The final session of each lesson was devoted to drawing conclusions and presenting documentation. To collect data, a researcher-made science learning achievement test (30 questions) was used. The test was designed based on the third-grade science textbook published in 2023. Test scores and the scoring of questions and performance were based on a five-point Likert scale (excellent: 5, good: 4, acceptable: 3, needs improvement: 2, very weak: 1). The validity of the instrument was confirmed by teachers and professors, and its reliability was determined using Cronbach's alpha, which yielded a coefficient of 0.865. Data analysis was conducted using SPSS software.FindingsBefore conducting a multivariate analysis of covariance (MANCOVA), the assumptions underlying this test were examined. Results of the normality test for the research variables (level 1, 2, and 3 science learning) in third-grade students indicated that all variables, both pre-test and post-test, met the assumption of normality, with significance levels greater than 0.05. Therefore, the use of parametric tests for the present data was appropriate. The results of the MANCOVA showed that the Reggio Emilia approach significantly increased third-grade students' science learning at all three levels: facts (F = 309.81, p = 0.001), basic concepts and skills (F = 150.67, p = 0.001), application of learning to new situations (F = 144.26, p = 0.001), and overall (F = 279.98, p = 0.001). Additionally, the effect size indicated that 85% of the difference between the experimental and control groups was attributable to the experimental intervention, namely the implementation of the Reggio Emilia approach (p < 0.001). Discussion and ConclusionThe findings of this study indicate that the Reggio Emilia approach can provide a conducive environment for science education, enabling students to acquire essential skills, concepts, and scientific facts through active and exploratory methods. Consequently, students can effectively apply these skills and experiences to novel situations and real-world contexts.Based on these results, it is recommended that, in addition to the primary teacher, greater attention be paid to students themselves and the learning environment as two additional teachers when implementing this approach in schools. Given that parents and community members are considered valuable resources in the learning process, it is suggested that appropriate platforms be established for interaction and collaboration with them. This would encourage parents to shift their focus from their children's knowledge and memorization to supporting their children in acquiring necessary skills and observing learning in real-life contexts. Considering that the Reggio Emilia approach is based on a curriculum that evolves according to the specific conditions, needs, interests, and abilities of students, it is recommended that textbook content be derived from students' lives and that each subject be centered around projects and skills-based activities. These activities should be designed to be undertaken individually or in groups, appropriate to students' ages. This aligns with Malaguzzi's belief that every child has a hundred languages through which they can express their abilities.